Gemella haemolysans bacteremia in a patient with secondary peritonitis due to a duodenal ulcer perforation: A case report - Hadano, Yoshiro (IDCases, 2018)
We describe a case of Gemella haemolysans septic shock in a 75-year old Japanese male with a duodenal perforation and secondary peritonitis. Blood cultures on admission were positive for Gram-positive and Gram-variable cocci, and G. haemolysans was identified using whole cell matrix-assisted laser desorpition/ionization mass spectrometry (MALDI-TOF MS), with a score value of 2.12. The 16S rRNA sequencing was difficult to use as a diagnostic test because there was more than 99% sequence homology with related bacterial strains. Based on both the biochemical profiles and whole groEL sequence, we concluded that the strain in our patient was G. haemolysans. The patient was successfully treated with a 16-day course of antimicrobials. His clinical condition improved, and no evidence of a relapse of the infection was noted. Although MALDI-TOF MS and 16S rRNA sequencing are useful for identification of the species, the basic biochemical profile is also important to identify a rare species.